93.0k views
5 votes
Two Algebra Questions! Help!

1) Divide 8x4 – 6x3 + 7x2 – 11x +10 by 2x – 1 using long division. Show all work. Then explain if 2x – 1 is a factor of the dividend.

2) Factor f(x) = x4 + x3 – 8x2 + 6x + 36 completely. Show all work for finding the factors. Sketch the graph by hand, use the graph below, label at least 6 points on the graph. State the factors and the roots. (Hint: two of your factors will be complex

1 Answer

0 votes

ANSWER TO QUESTION 1

Check attachment for long division.


From our long division we can write the following;



(8x^4-6x^3+7x^2-11x+10)/(2x-1) =4x^3-x^2+3x-4+(6)/(2x-1)


Since the polynomial



8x^4-6x^3+7x^2-11x+10 leaves a non zero remainder of
6 when divided by
2x-1, we conclude that
2x-1 not a factor of the dividend,


ANSWER TO QUESTION 2


We want to factor


f(x)=x^4+x^3-8x^2+6x+36

The possible rational roots are;


\pm1, \pm 2,\pm 3, \pm 4,\pm 6,\pm 9, \pm18, \pm 36


We found



f(-2)=(-2)^4+(-2)^3-8(-2)^2+6(-2)+36



f(-2)=16+-8-32+-12+36


f(-2)=-36+36



f(-2)=0


and



f(-3)=(-3)^4+(-3)^3-8(-3)^2+6(-3)+36



f(-3)=81-27-72-18+36



f(-3)=-36+36



f(-3)=0.


This means that
(x+2) and
(x+3) are factors of the polynomial.


This also means that


(x+2)(x+3)=x^2+5x+6 is also a factor of the polynomial


So we apply long division to obtain the remaining factors as shown in the attachment.



\Rightarrow f(x)=x^4+x^3-8x^2+6x+36=(x+2)(x+3)(x^2-4x+6)



We factor further to obtain;


\Rightarrow f(x)=x^4+x^3-8x^2+6x+36=(x+2)(x+3)(x-(2-√(2)i))(x-(2+√(2)i))








Two Algebra Questions! Help! 1) Divide 8x4 – 6x3 + 7x2 – 11x +10 by 2x – 1 using long-example-1
Two Algebra Questions! Help! 1) Divide 8x4 – 6x3 + 7x2 – 11x +10 by 2x – 1 using long-example-2
User Cjg
by
5.0k points